2021
DOI: 10.3389/fpubh.2020.570832
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fertility Behaviors on Depression Among the Elderly: Empirical Evidence From China

Abstract: Background: Increased population aging is associated with increased incidence of depression among the elderly. Existing studies have shown that ill-advised fertility behaviors during their youth also affect the health of the elderly. However, insufficient attention has been paid to depression among elderly in China. This paper focuses on how fertility behaviors affect senile depression among parents by examining the heterogeneity of such effects and tests the applicability of existing theoretical findings in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…For many countries, the older adults are the main consumers of medical resources, and the health problems of older adults have become a hot spot of the whole society and the main targets of various countries’ health policies[ 3 ] [ 5 , 6 ]. The older adults are the high-risk group of mental health, and depression is the most common mental illness in the older adults, which will increase the risk of suicide and death of them [ 7 – 9 ]. In today's call for healthy aging, the problem of depression of the older adults has become a major research area, and alleviating the depression of the older adults has become one of the ways to achieve healthy aging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For many countries, the older adults are the main consumers of medical resources, and the health problems of older adults have become a hot spot of the whole society and the main targets of various countries’ health policies[ 3 ] [ 5 , 6 ]. The older adults are the high-risk group of mental health, and depression is the most common mental illness in the older adults, which will increase the risk of suicide and death of them [ 7 – 9 ]. In today's call for healthy aging, the problem of depression of the older adults has become a major research area, and alleviating the depression of the older adults has become one of the ways to achieve healthy aging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…High parity and early childbearing increased the risk of breast cancer ( 48 ), liver disease ( 49 ), and arthritis ( 50 ). High parity was also associated with higher factor scores of respiratory-psychiatric pattern diseases, such as asthma ( 51 ) and depression ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the positive effects of PA on depression via direct and indirect pathways [19,20]. Previous studies have suggested that parity may be a factor in depression [21,22], although the relationship between speci c births and the risk of depression is inconsistent. Therefore, examining the PA-depression-cognitive function pathway may be helpful in further understanding the varied bene ts of PA on cognitive function in women with different parity status.…”
Section: Introductionmentioning
confidence: 99%